Elevational shifts in phylogenetic diversity of angiosperm trees across the subtropical Brazilian Atlantic Forest. (23rd December 2020) - Bergamin, Rodrigo S.; Seger, Guilherme D. S.; Carlucci, Marcos B.; Molz, Martin; Mello, Ricardo S. P.; Martins, Rafael; Jarenkow, João A.; Brack, Paulo; Müller, Sandra C.; Duarte, Leandro D. S.
Abstract: Elevation gradients are drivers of species diversity, and, recently, studies have considered the evolutionary process in shaping community assembly patterns. Patterns of plant species richness across elevational gradients have been studied in different parts of the Atlantic Forest; however, little is known about plant phylogenetic diversity patterns. Thus, we aimed to analyse the phylogenetic diversity of angiosperm trees along an elevation gradient in southern Brazilian Plateau, in the subtropical portion of the Atlantic Forest. We expected a decrease in phylogenetic diversity along the elevation gradient, from lowlands towards to highlands, where species may be evolutionary closely related as many tropical lineages are not capable to inhabit colder conditions. We also investigated the distribution of phylogenetic clades along the elevation gradient through principal coordinates of phylogenetic structure. Data were obtained from 28 phytosociological surveys distributed across different elevation levels, ranging from 40 to 975 m. We found a negative association between phylogenetic diversity and the elevation gradient. The representativeness of families Myrtaceae and Lauraceae increased with elevation, while most of the families decreased in species richness and are replaced by temperate families such as Winteraceae ( Drimys ) in higher elevations. The decrease in phylogenetic diversity with increasing elevation may be linked to niche conservatism of tropical lineages that retain their historical climatic niches and thus many species are not capable to inhabit colder environments. Most tropical clades are restricted to lower elevations; however, Myrtaceae and Lauraceae probably evolved tolerance to colder temperatures during glacial cycles. Furthermore, the probably long‐term climate stability in lowlands than highland areas may have promoted the co‐occurrence of distantly related species, resulting in higher phylogenetic diversity. Finally, we observed how historical imprints and current environmental conditions shape the phylogenetic diversity of angiosperm tree species in subtropical Atlantic Forest.